In defense of fractional free banking: Back to fundamentals - Posvanc, Matus (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2021)
This paper examines the debate between the so-called fractionalists and the reservists within the Austrian School of Economics (1994 – 2005), emphasizing the maturity mismatch problem (2009 – 2019). It focuses on the fundamental arguments: the ontological view on currencies as banks’ products (IOUs) and money, the purchasing power of money, and the maturity mismatch problem. Banking activity is seen as a vital evolutionary superstructure humans use to determine the marginal utilization of existing capital resources, effectively discovering the coincidence of money interest towards natural interest levels and time preferences within society. The thesis advocates the superiority of fractional and free banking over the reservist alternative. It shows that fractional free banking is not based on property rights violations, and does not cause systematic economic cycles beyond those related to natural business errors.